Mengungkap Makna Akuntansi Pada UMKM di Kota Palangka Raya - Kharisma Nugraha Putra; Verra Rizki Amelia; Dhina Sri Widyaningsih; Theresia Mentari; Rinto Alexandro (FKIP, Universitas Palangka Raya, 2023)
The use of accounting information or the availability of financial reports used by SMEs in making business decisions is an important factor supporting business success. This study aims to gain an understanding of the meaning of accounting and accounting phenomena in SMEs in Palangka Raya City. The research subjects used in this study were Micro, Small, and Medium Enterprises (SMEs) in Palangka Raya City with the provision that SMEs are partners of the Regional Office of the Directorate General of Treasury in Central Kalimantan, SMEs have been running for more than two years, and SMEs have an understanding of research phenomenon. The results of the study show that accounting is interpreted as 1) information, 2) accountability, and 3) a means of communication. The accounting phenomenon that exists in SMEs in Palangka Raya City as a whole has implemented accounting practices in their business activities, although financial records carried out by SMEs actors tend to be simple, this has an impact on ongoing accounting practices that are still not under the accounting cycle perfectly.